Correlation of some of the Friedel-Crafts' reaction - McGechen, John Finnie (The University of Edinburgh, 1930)
1. The proportions of m- and p-tert.-butyl-toluenes produced in the reaction between tert.-butyl chloride and toluene with aluminium chloride as catalyst have been estimated. 2. The proportions of m- and p-tert.-butyltoluenes in the same reaction with ferric chloride as catalyst have been estimated. 3. The observation of Bialobrzewski was shown to be definitely wrong by proving that m-tert.-butyltoluene was a product of the reaction mentioned in (2), and that it was present to the extent of 65$ of the total monosubstituted derivatives. 4. The reaction between n-butyl chloride and toluene was carried out for the first time, and mand p-sec.-butyltoluenes shown to be products of the reaction. 5. The reactions between n-butyl chloride and both chloro- and bromobenzenes were carried out for the first time, and m- and p~derivatives of the halogeno-benzenes shown to be formed in both cases. 6. tert.Butyl chloride and bromobenzene, when allowed to react' in presence of aluminium chloride, were shown to produce m- and p-bromo-tert.-butylbenzenesin a proportion of 70% to 30% respectively, which disagrees with the result of Boedtker who reported that the p-derivative only was formed.
The correlation of some of the Friedel-Crafts' reaction